2016
DOI: 10.1148/radiol.2015150160
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Cerebral Microhemorrhages in Military Service Members with Chronic Traumatic Brain Injury

Abstract: Purpose-To detect cerebral microhemorrhages in military service members with chronic traumatic brain injury by using susceptibility-weighted magnetic resonance (MR) imaging. The longitudinal evolution of microhemorrhages was monitored in a subset of patients by using quantitative susceptibility mapping.Materials and Methods-The study was approved by the Walter Reed National Military Medical Center institutional review board and is compliant with HIPAA guidelines. All participants underwent two-dimensional conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 20 publications
(23 reference statements)
1
48
0
Order By: Relevance
“…The susceptibility changes following the treatment may also be admixed with changes related to the natural evolution of hematoma susceptibility over time. However, a recent study on monitoring microhemorrhage magnetic susceptibility changes reported that the susceptibility decreased over time: –0.1 ± 0.14 ppb per day . Therefore, the observed susceptibility value change varying from –10 ppb up to –260 ppb are mainly attributed to treatment.…”
Section: Discussionmentioning
confidence: 94%
“…The susceptibility changes following the treatment may also be admixed with changes related to the natural evolution of hematoma susceptibility over time. However, a recent study on monitoring microhemorrhage magnetic susceptibility changes reported that the susceptibility decreased over time: –0.1 ± 0.14 ppb per day . Therefore, the observed susceptibility value change varying from –10 ppb up to –260 ppb are mainly attributed to treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Since QSM is very sensitive to blood products, it can clearly identify local damage in complicated mTBI, whereby shearing forces can cause diffuse axonal injury (DAI) patterns that manifest as hemorrhages and contusions 9 . The potential utility of QSM in assessing uncomplicated mTBI is more nuanced.…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying the isotropic magnetism of brain tissue can reveal changes in components such as ferretin, hemosiderin, water content, myelin, and calcium 7;8 . Along with conventional SWI, QSM has already been used to identify regions of focal tissue damage in complicated mTBI in cohorts of military personnel 9 and civilians 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, the long-term clinical risks and management in patients with microbleeds have yet to be defined. This remains an active area of investigation, where QSM can play an important role, particularly in longitudinal studies of microbleed burden (220). …”
Section: Clinical Applications Enabled By Qsm Biometal Imagingmentioning
confidence: 99%